The Effectiveness of Context Structure Sound Dictionary Strategy to Improve Vocabulary Mastery at the Eighth Grade Students of SMP Negeri 1 Alian Kebumen in the Academic Year of 2015/2016 - Eva Meilina (Scripta : English Department Journal, 2019)
The aim of this research is to know whether context structure sound dictionary strategy is effective or not to improve vocabulary mastery at the eighth grade students of SMP Negeri 1 AlianKebumen in the academic year of 2015/2016. This experimental research was being carried out at SMP Negeri 1 AlianKebumen from 29 July to 19 August 2015. Here, the researcher took the data from the eighth grade students VIII A and VIII B as the sample of the research. VIII A class is as a control group that consists of 32 students, and VIII B class is as an experimental group consists of 32 students. The researcher has collected the data by giving pre-test and posttest to the sample. The result of the test has been analyzed by using SPSS. The result of this research shows that using context structure sound dictionary strategy is effective for improving vocabulary mastery. It is proven that the result of t-value based on the critical value of t-table by using 5% (0.05) significance level, the value of t-table 2.00. It means that t-value is higher than t-table (2.44 > 2.00). It can be seen from gain score control group and experimental group. The experimental group is higher than control group. Based on the result above, it can be concluded that context structure sound dictionary is effective to improve vocabulary mastery at the eighth grade students of SMP Negeri 1 AlianKebumen in the Academic Year of 2015/2016.